Drying kinetics and particle formation of potato powder during spray drying probed by microrheology and single droplet drying. (February 2019) - Tan, Yaoyao; Zhao, Yue; Hu, Honghai; Fu, Nan; Zhang, Chunjiang; Zhang, Hong; Dai, Xiaofeng
Graphical abstract: Unlabelled Image Highlights: Potato slurry stability and particle motion were monitored by microrheology. Temperature, mass, and morphology profile during drying was analyzed by SDD. Insoluble content affected droplet drying by prevent the crust shrinkage.